(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Nanomedicine is the application of nanotechnology in the field of medicine. Nanoparticles are distinguished by their enormous surface area that facilitates interaction with a variety of functional ligands. Metallic nanoparticles have also been used for medicine delivery, diagnostic imaging, labeling, and biosensors since they are compatible with biological systems. Metallic nanoparticles created using biological agents including fungus, plants, bacteria, and other microorganisms are very stable.